Analogue Rice Formulation from Tapioca, Soybean Flour, Natural Dyes (Amaranthus tricolor L. and Alternanthera amoena V.) - Saati, Elfi Anis; Noviani, Auliarinda; Wachid, Muhammad; Siskawardani, Devi Dwi (Food Science and Technology Journal (Foodscitech), 2020)
The diversification of food is the solution of rice imports elevation, rice consumption dependence, as well as lack of protein calories for baby in Indonesia. Analogue rice from local resources such as various starches, both from tubers and nuts. Analogue rice is produced from flour with the addition of water or other nutritional components. To improve consumer appeal, the natural dyes addition also can increase nutrition product. This research aimed to analyze the effect of pigment sources and formulation of tapioca and soybean. Nested design was applied with 1st factor was sources of pigment (control, extracted green spinach, and red spinach). The second factor was the proportion of tapioca and soybean flour. The result showed that protein increased from 4.54% to 5.30% and iron (Fe) increased from 2.58 to 14.54 ppm. The best analog rice was produced from T1B2 (85% tapioca : 15% soybean flour x red spinach) which had moisture content (4.96%), fat (3.23%), protein (5.70%), absorption capacity (175.89%), color intensity (L = 52.40; a+ = 1.50; b+ = 10.10), antioxidant activity (88.55%), total pigment (4.86 mg L-1), and iron (20.11%). The organoleptic score was taste (3.17 = quite like), texture (3.30 = quite like), shape (3.03 = quite like), and preference (3.23 = quite like).